2020
DOI: 10.1039/d0sc02547j
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemically assisted hydrolysis in the ADOR process

Abstract: Efficient hydrolysis of zeolites in the ADOR process using mechanochemistry, including economical enrichment with 17O for solid-state NMR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 78 publications
1
21
0
Order By: Relevance
“…Their high molecular weight, bulk and low framework polarity also means that they are poorly soluble and are most appropriately used in heterogenous reactions, either A particularly intriguing approach is to exploit the 17 of the local structure (resulting from the presence of residual water in the interlayer space) continued even after the "final" IPC-2P product was formed, despite no obvious changes in the powder XRD pattern (or indeed the 29 Si NMR spectrum) over this period. A similar reaction was studied by Rainer et al, 61 using mechanochemistry. 17 Recent work has also investigated the lability of conventional (i.e., non ADOR-able) zeolite frameworks in ambient aqueous conditions using 17 O NMR spectroscopy, with MAS and MQMAS spectra used to follow the (in situ) enrichment of MOR, FER and CHA frameworks by reaction with H 2 17 O(l) at room temperature.…”
Section: Exploring Chemical Reactivity Using 17 O Nmrmentioning
confidence: 73%
See 2 more Smart Citations
“…Their high molecular weight, bulk and low framework polarity also means that they are poorly soluble and are most appropriately used in heterogenous reactions, either A particularly intriguing approach is to exploit the 17 of the local structure (resulting from the presence of residual water in the interlayer space) continued even after the "final" IPC-2P product was formed, despite no obvious changes in the powder XRD pattern (or indeed the 29 Si NMR spectrum) over this period. A similar reaction was studied by Rainer et al, 61 using mechanochemistry. 17 Recent work has also investigated the lability of conventional (i.e., non ADOR-able) zeolite frameworks in ambient aqueous conditions using 17 O NMR spectroscopy, with MAS and MQMAS spectra used to follow the (in situ) enrichment of MOR, FER and CHA frameworks by reaction with H 2 17 O(l) at room temperature.…”
Section: Exploring Chemical Reactivity Using 17 O Nmrmentioning
confidence: 73%
“…6d ) after the initial reaction indicated that rearrangement of the local structure (resulting from the presence of residual water in the interlayer space) continued even after the “final” IPC-2P product was formed, despite no obvious changes in the powder XRD pattern (or indeed the 29 Si NMR spectrum) over this period. A similar reaction was studied by Rainer et al , 61 using mechanochemistry. 17 O NMR spectra showed enrichment of the Si– 17 O–Si linkages in UTL after only ∼30 min (at 150 rpm), with the presence of a signal thought to be attributable to Si– 17 O–Ge at short reaction times (which has not yet been observed in hydrothermal reactions).…”
Section: Exploring Chemical Reactivity Using 17 O Nmrmentioning
confidence: 73%
See 1 more Smart Citation
“…This peak corresponds to the d 200 Please do not adjust margins Please do not adjust margins interlayer distance and is commonly followed in ADOR reactions to observe the distance between the silica-rich layers and therefore identify the ADOR product present. 23 The 2θ position (Figure S3) around 7.35° indicates that the product at the end of the data collection is IPC-2P, the partially connected intermediate of IPC-2, with a typical peak position around 7.5°. 12 The proposed final product of IPC-2P is further supported by in-house PXRD data of the recovered hydrolysis sample (from the APS) and the following calcination to produce IPC-2 (Figure S4).…”
Section: Resultsmentioning
confidence: 98%
“…In the mechanochemically assisted approach, known products of the ADOR process were afforded without the need for a heating source, in only 30 min and with a significantly decreased amount of liquid. 126 Interestingly, in this new method the highest acid concentrations (12 M HCl) led to the denser PCR framework (Fig. 8), in contrast to the usually obtained OKO structure.…”
Section: Dalton Transactionsmentioning
confidence: 74%